Gas price shocks and euro area inflation - Jakob Feveile Adolfsen; Massimo Minesso Ferrari; Jente Esther Mork; Ine Van Robays (European Central Bank (ECB), 2024)
This paper develops a Bayesian VAR model to identify three structural shocks driving the European gas market: demand, supply and inventory shocks. We document how gas price fluctuations have a heterogeneous pass-through to euro area prices depending on the underlying shock driving them. The pass-through is stronger and more persistent when gas prices are driven by aggregate demand or supply pressures, while inventory shocks have a weaker impact. Supply shocks, moreover, are found to pass through to all components of euro area inflation - producer prices, wages and core inflation, which has implications for monetary policy. We finally document how the response of gas prices to shocks is non-linear and is significantly magnified in periods of low unemployment.
Keywords: C50; C54; E30; E31; Q43; 330; Gas Price; Pass-through; Price; Euro Area